Pengaruh Faktor-faktor Yang Terjadi Pada Kerja Lembur Terhadap Kualitas Pekerjaan - Joice Batara; Josefine Ernestine Latupeirissa; Meti (Program Studi Teknik Sipil UKI Paulus-Makassar, 2022)
A construction project is a series of interrelated activities to achieve certain goals within a certain time, cost and quality limit. The purpose of this study is to analyze the factors that occur in overtime work and affect the quality of work on casting beams and plates on the second floor of the Trans Studio Makassar New Developmentproject. There are main factors that occur in overtime and affect the quality of work that can be concluded, namely: Factors of strict supervision at work, Factors of lack of labor expertise, Factors of worker inefficiencies due to too much work to be completed, Factors of lack of workers' rest time, Lighting factors when doing overtime work at night and Factors The existence of job guarantees can increase the morale of workers.